Analysis of the Family of Hope Program in Protecting the Homeless to Create a Welfare State - Ilham Fawwaz Samseno; Agus Riwanto (International Journal of Advance Social Sciences and Education (IJASSE), 2023)
The purpose of the study is to analyze the Family Hope (PKH) program in protecting the homeless in order to raise the level of the homeless economy from the perspective of the welfare state. PKH is a conditional cash direct funding program implemented by the Ministry of Social Affairs to improve public welfare, especially in the education and health sectors. The research method used is literature research, through the collection of information from various reliable sources related to PKH and the concept of the welfare state. The results of the analysis show that PKH can be considered as an approach to social protection of the homeless in the context of the welfare state. PKH aims to reduce poverty and improve quality of life through access to education. To improve the effectiveness of PKH, it is necessary to strengthen cooperation between agencies such as the Ministry of Social Affairs, Ministry of Health and Ministry of Education and culture. The legal basis used is Law No. 11 of 2009 on social welfare, Article 33 of the 1945 Constitution after amendment, and Menkokesra decision, namely: No. 031/KEP/MENKO/-KESRA/IX/2007 in addition, good coordination between Related Agencies will help optimize available resources and minimize obstacles in the implementation of social welfare programs. In addition, it is also important to improve the monitoring system and periodic evaluation of the implementation of PKH, in order to ensure that the program is carried out, according to the desired goals and provide optimal benefits to the community.